2018
DOI: 10.1017/jfm.2018.833
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling the effects of aspect ratio, Reynolds number and Rossby number on a rotating insect-wing planform

Abstract: The individual and combined influences of aspect ratio ($A$), Reynolds number ($Re$) and Rossby number ($Ro$) on the leading-edge vortex (LEV) of a rotating wing of insect-like planform are investigated numerically. A previous study from our group has determined the wingspan to be an appropriate length scale governing the large-scale LEV structure. In this study, the $A$ range considered is further extended, to show that this scaling works well as $A$ is varied by a factor of 4 ($1.8\leqslant A\leqslant 7.28$)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…This range is scaled to, approximately, , based on the wingspan (b) and the mean velocity at the radius of gyration (R g ). This span-based scaling of the Reynolds number (Re b ) has been shown to appropriately govern the large-scale flow structures over a wing in our recent studies (Harbig, Sheridan & Thompson 2013;Bhat et al 2019). In the case of flapping wings, Re b is defined as…”
Section: Methodsmentioning
confidence: 85%
“…This range is scaled to, approximately, , based on the wingspan (b) and the mean velocity at the radius of gyration (R g ). This span-based scaling of the Reynolds number (Re b ) has been shown to appropriately govern the large-scale flow structures over a wing in our recent studies (Harbig, Sheridan & Thompson 2013;Bhat et al 2019). In the case of flapping wings, Re b is defined as…”
Section: Methodsmentioning
confidence: 85%
“…Several studies examining the aerodynamic effects of varying S have reported contradictory findings. While some studies found little variation in force coefficients (Usherwood & Ellington, 2002; Luo & Sun, 2005; Garmann & Visbal, 2014), others have postulated that larger wing spans are detrimental for force generation (Harbig et al, 2012; Han, Chang & Cho, 2015; Bhat et al, 2019). All these studies considered solid wings at Re c >100.…”
Section: Discussionmentioning
confidence: 99%
“…The LEV evolution depends on , and (see Bhat et al. (2019), who determined that these effects are best isolated using span-based definitions of and ), but often exhibits arch-like liftoff outboard and further LEVs forming ahead of the main one (e.g. Jardin, Farcy & David 2012; Harbig, Sheridan & Thompson 2013; Garmann & Visbal 2014; Carr et al.…”
Section: Modelmentioning
confidence: 99%
“…2016 a ; Bhat et al. 2019). However, the LEV remains close to the wing over much of the span and the overall flow exhibits a growing vortex loop for up to , albeit with complex outboard structures (Garmann & Visbal 2014; Carr et al.…”
Section: Modelmentioning
confidence: 99%